Simulação da produção de biodiesel via destilação reativa: avaliação de parâmetros operacionais no Aspen Plus® - de Abreu Nabo, Victor Miguel; Dellosso Penteado, Eduardo; da Silva Martins, Luiza Helena; Rocha de Oliveira, Johnatt Allan; Komesu, Andrea (Latin American Journal of Energy Research, 2025)
Given the increasing investment in renewable energy sources to meet population demand and promote environmental conservation, biofuel production has gained prominence in energy sector research. In particular, biodiesel production stands out due to its high yield, achieved through the conversion of vegetable- or animal-derived oils. The transesterification reaction is the primary process for biodiesel production and can be conducted using different approaches, such as reactive distillation. This technique allows for the integration of reaction and chemical separation stages within a single unit, optimizing energy use and reducing biodiesel purification costs. In this context, this study aimed to perform a computational simulation of the transesterification reaction via reactive distillation to assess the feasibility of biodiesel production using the Aspen Plus® simulator. The key parameters influencing biofuel conversion were analyzed, such as the conversion of reactants relative to the added alcohol (alcohol-to-oil ratio) and reflux ratio. Under optimal conditions, a biodiesel conversion of 89.1% was achieved, using a reflux ratio of 0.2, a methanol-to-oil ratio of 15:1, and a methanol feed flow rate of 96.75 kmol/h, resulting in a biodiesel molar flow rate of 18.186 kmol/h in the product stream.